If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+x+5=6
We move all terms to the left:
2x+x+5-(6)=0
We add all the numbers together, and all the variables
3x-1=0
We move all terms containing x to the left, all other terms to the right
3x=1
x=1/3
x=1/3
| q/4=-2.4 | | v-6/2=-10 | | 1.33x-8=2.66x-6 | | 5x+9=13+x | | 20–5m=4+3m | | -8-m=1 | | 8*x+4=22*3 | | 5x+40=x+20 | | 6+2x=3x-6 | | 7*y=45 | | 5-3x+60=5 | | 5x+13=6x+10 | | 2(x+4)=4x+7-2x+1 | | 6x+26=5x-1 | | 9x-5=10x-14 | | 4x+26x-7=6(5x+9) | | -10+p/2=-12 | | x×x=63 | | x/8=3=12 | | b+2/3=7/3 | | b+2/3=4/1/3 | | g=68 | | -16=8v+2(v+7) | | X2+5x-31=5 | | 3(5x+4)-8x=7x-12 | | x/7=7.04/4 | | 7x+1+11x-18+5x+13=88 | | 0x+9=8x+4 | | 4(z-9)=17 | | 7z=42;z=8 | | 5x−10=90 | | x+9x=100 |